"For a colleen's complexion": soap and the politicization of a brand personality, 1888-1916. (11th February 2014) - Philip O'Connor, John
Abstract : Purpose: – The aim of this paper is to examine how the "colleen" archetype was used in the creation of a successful brand personality for a range of soap manufactured in Ireland during the early twentieth century. It reveals the commercial and political agendas behind this move and the colleen's later application to Ulster unionist graphic propaganda against Home Rule between 1914 and 1916. Design/methodology/approach: – This case study is based on an analysis of primary and secondary sources; the former encompassing both graphic advertising material and ephemera. Findings: – This paper demonstrates how contemporary pictorial advertising for colleen soap was suffused with text and imagery propounding Ulster's preservation within the UK. It also suggests that the popularity of this brand personality may have been a factor in the colleen's appropriation for propaganda purposes by certain strands within Ulster unionism. Originality/value: – This paper is based on original research that expands the historical corpus of Irish visual representation, while also adding notably to discourses within the History of Marketing and Women's History.